2019
DOI: 10.2217/pgs-2018-0156
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 Genotype, Physician Prescribing Pattern, and Risk for Long QT on Serotonin Selective Reuptake Inhibitors

Abstract: To examine the impact of CYP2C19 genotype on selective serotonin reuptake inhibitor (SSRI) prescribing patterns. Patients & methods: Observational cohort containing 507 unique individuals receiving an SSRI prescription with CYP2C19 genotype already in their electronic medical record. Genotype was distributed as follows: n = 360 (71%) had no loss of function alleles, 136 (26.8%) had one loss of function allele and 11 (2.2%) had two loss of function alleles. Results & conclusion: For poor metabolizers exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Challenges include a lack of understanding of the ontogeny of drugmetabolizing enzymes and transporters in different phases of human development, lack of integration into clinical trials, lack of definitive guidelines for this patient population, understanding of the economic value of testing, and deciphering the multivariate nature of most drug effects with the contribution of physiological and pathological factors. 18,25 One final consideration of significance for the study is based on a point brought up by Brown, et al, as much of this implementation research occurs within large-scale children's specialty institutions; this study sought trends found in a small, rural inpatient facility. Regardless of the size or scale of the facility, one thing is for certain: to have the best chance at proper utilization of PGx in pediatric populations, there needs to be an increase in the education across all professional levels to provide the most effective and accurate knowledge on the subject to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges include a lack of understanding of the ontogeny of drugmetabolizing enzymes and transporters in different phases of human development, lack of integration into clinical trials, lack of definitive guidelines for this patient population, understanding of the economic value of testing, and deciphering the multivariate nature of most drug effects with the contribution of physiological and pathological factors. 18,25 One final consideration of significance for the study is based on a point brought up by Brown, et al, as much of this implementation research occurs within large-scale children's specialty institutions; this study sought trends found in a small, rural inpatient facility. Regardless of the size or scale of the facility, one thing is for certain: to have the best chance at proper utilization of PGx in pediatric populations, there needs to be an increase in the education across all professional levels to provide the most effective and accurate knowledge on the subject to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, variability in pharmacokinetic genes can lead to serious adverse outcomes for many of the drugs discussed in this review. Cytochrome P450 (CYP) 2C19, for example, metabolizes 5–10% of all prescription drugs, and loss of function alleles at the CYP2C19 gene locus are known to increase risk for potentially lethal ventricular arrhythmias in patients using three commonly prescribed SSRIs: sertraline, citalopram, and escitalopram [ 49 , 50 ]. Furthermore, loss of function alleles at the CYP2D6 locus increase patient risk for ventricular arrhythmias in the context of three other SSRIs: fluoxetine, fluvoxamine, and paroxetine [ 49 , 51 ].…”
Section: The Need For Risk Stratificationmentioning
confidence: 99%
“…However, the implementation of these tests is currently based on known association with severe adverse drug reactions other than SIADH. For example, decision support already exists within electronic medical records at some academic institutions to optimize the efficacy of SSRIs and reduce the frequency of adverse events such as electrocardiographic abnormalities associated with their use [ 50 , 56 ]. It is highly likely that the same gene-based dosing approach would reduce the frequency of SIADH associated with the use of SSRIs.…”
Section: The Need For Risk Stratificationmentioning
confidence: 99%
“…In this situation, some clinicians monitor patients on SSRIs using serial electrocardiograms (EKGs) rather than changing the prescription. The key to this approach is the availability of an endophenotype [ 49 ].…”
Section: Promisesmentioning
confidence: 99%